Food Safety Overview In The Production of Roasted Chicken Legs For Ci Airlines AT PT. AFD - Oka Jiwantara Gusti Ngurah; Ni Made Ayu Suardani Singapurwa; Anak Agung Made Semariyani (Warmadewa University Press, 2025)
HACCP system is a preventive approach in ensuring food safety that is applied by PT AFD in the production of Roasted Chicken Leg menu for airlines. This study was conducted through observation of the production stages and identification of critical control points (CCPs). There are five main CCPs that are strictly controlled, namely the receipt of cold/frozen ingredients, storage, cooking process, blast chilling, and portioning. Observations show that all stages have met HACCP standards, with the support of seven OPRPs to keep the environment and work practices hygienic. The role of Quality Control is vital, but the collaboration of the entire production team is also key to the successful implementation of this system.